The diminution of capillary luminal area within dermal microcirculation and its association in diabetic foot ulcer patients - Mohd Radzuan, Hazulin; Myint, Yi Yi; Tun, Ye; Zulkifly, Ahmad Hafiz (2012)
The reduction of capillary luminal area within dermal microcirculation in diabetic foot patients contributes towards the development of foot ulceration and subsequent failure to heal existing ulcers. We studied 42 subjects, involving 10 controls, 16 patients with neuropathic ulcer and 16 patients with neuroischaemic ulcer. The specimens were taken by using skin punch biopsy and were routinely processed for light microscopy. The mean capillary luminal area (LA) and outer area (OA) were performed by calculating and measuring 3 selected capillaries in each slide of every patient and their percentages of ratio were recorded. We noted that there was significant decrement in percentages of LA:OA among the diseased group as compared to the controls, F(2, 39)=17.54, p<0.05. The Tukey post-hoc comparisons showed that the percentages of LA:OA of neuroischemic group (M=31.89, 95% CI [24.79, 39.00]) was significantly reduced as compared to neuropathic group (M=41.76, 95% CI [37.69, 45.82]) since p<0.05. In conclusion, the reduction of dermal capillary luminal area among diabetic foot patients could be due to the alteration in the microvascular hemeorheology, causing basement membrane thickening as the results of the metabolic disease.